Hubungkait antara tekanan kerja dan kepuasan kerja dengan komitmen di kalangan guru Sekolah Menengah di Negeri Perlis - Norzafirah, Rosli (2017)
Job stress and individual job satisfaction are often discussed and become an important issue. It can effect individual career commitment. However, past studies in this area are more focused on the private sector and less emphasis and given in the public sector. This attracted the researcher to carry out the study in the public sector and the focus of research was on teachers. The researcher conducted a study on the relationship between independent variables of stress and job satisfaction on the dependent variable commitment. The respondents in this study involved of 343 secondary school teachers in Perlis. A total of 343 questionnaires were distributed and out of that total only 205 questionnaires were returned within a response rate of 60%. A total of 49 items were formed using a five-point Likert scale. The data were analyzed using Statistic Package for Social Science (SPSS) version 22.0 using descriptive analysis and inferential analysis that is correlation analysis, regression and reliability test also analysis factor. The results showed the relationship between job stress and job satisfaction with commitment were significantly related.